La aplicación de métodos musicales activos y su relación en la formación de los estudiantes de la carrera de música, modalidad semipresencial del área de la Educación, el Arte y la Comunicación de la Universidad Nacional de Loja, periodo 2008-2009. Lineamientos alternativos - Terán Ludeña, Lorena Cecilia (2010)
This present research has as a general deal to detect what active methods are applied by teachers, and their incidence in the educators-in-training of the Musical Education Career, at a semi distance mode of the AEAC of the National University of Loja. The methods that are used in this investigation were: The scientific method, analytic-synthetic one, and the descriptive method for the analysis. The applied technique was the inquire to graduate teachers from 2008-2009, and students from the Musical Career, at a semi distance mode. The results obtained from the inquiries that were applied to people determine that teachers are not using the active musical methods in a proper way to educators-in-training of such career. Therefore, all of these results have guided us to set up the alternate proposal in order to improve the knowledge of the active musical methods and so they can be applied properly and effectively to educator-in-training of this career, and in this way, to develop their skills and abilities in the Musical Teaching.